Studi Literatur: Analisis Teori Kontemporer Akuntansi Perbankan Syariah - Nur Ika Mauliyah (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2021)
This research is a literature study that discusses Islamic banking accounting theory analysis. Islamic banking accounting at this time is an action taken when conventional accounting does not fulfill the wishes of some Indonesian people who are Muslim. The offer provided by the Islamic economy is the best choice because banks have so far only wanted the maximum possible profit but lacked a humanist side to their customers. Products provided by Islamic banking such as mudharabah, musyarakah, wadi'ah, ijarah, wakalah, and so on. Sharia accounting reporting must uphold Islamic values in accordance with Islamic provisions so that there is no element of fraud in it. The accounting stage has an impact on management, owners, employees, and customers. Islamic accounting practice wants to implement a business environment that instills religious elements such as theological, humanist, and transcendental.